2023
DOI: 10.18388/abp.2020_6692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artemisinin combined with allicin on improving cardiac function, fibrosis and NF-κB signaling pathway in rats with diabetic cardiomyopathy

Abstract: Myocardial fibrosis and inflammation cause cardiac hypertrophy, arrhythmias, and heart failure in diabetics, a leading cause of mortality. Since it’s complicated, no drug treats diabetic cardiomyopathy. This research examined the effects of artemisinin and allicin on heart function, myocardial fibrosis, and the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathway in diabetic cardiomyopathy rats. A total of 50 rats were separated into 5 groups, 10 of which were the control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Recent research indicated that Toll-like receptor 4 (TLR4) and the nuclear factor kappa B (NF-κB) signalling pathway play a role in promoting the activation of cytokines such as TNF-α, IL-6, and IL-1β to exacerbate inflammation, leading to subsequent myocardial tissue damage [ 18 ]. Inhibition or absence of TLR4 or NF-κB, which are critical regulators in pro-inflammatory cascades, had been shown to reduce left ventricular remodelling extent and improve cardiac function [ 19 ]. Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is an essential protein involved in regulating intracellular calcium transport processes and cardiomyocyte contractile function.…”
Section: Allicin In the Treatment Of Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research indicated that Toll-like receptor 4 (TLR4) and the nuclear factor kappa B (NF-κB) signalling pathway play a role in promoting the activation of cytokines such as TNF-α, IL-6, and IL-1β to exacerbate inflammation, leading to subsequent myocardial tissue damage [ 18 ]. Inhibition or absence of TLR4 or NF-κB, which are critical regulators in pro-inflammatory cascades, had been shown to reduce left ventricular remodelling extent and improve cardiac function [ 19 ]. Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) is an essential protein involved in regulating intracellular calcium transport processes and cardiomyocyte contractile function.…”
Section: Allicin In the Treatment Of Cvdmentioning
confidence: 99%
“…NF-κB serves as a prototypical pro-inflammatory signalling pathway capable of activating the TGF-β pathway to facilitate myocardial fibrosis [ 69 ]. Kong et al [ 19 ] found that allicin alleviated cardiac dysfunction and decreased myocardial fibrosis in STZ-induced diabetic rats by inhibiting the NF-κB signalling pathway (Table 5 ).…”
Section: Allicin In the Treatment Of Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that AG has the potential to treat DCM by reducing inflammation and oxidative stress, and its mechanism may be related to NF-κB and NOXs/Nrf2 signaling pathways. Artemisinin and allicin (AA) have anticancer, antioxidant, and anti-inflammatory biological activities ( Zhou et al, 2022 ; Jin et al, 2023 ) and have been proved to be used in clinical anti-myocardial fibrosis ( Kong et al, 2023a ). Kong et al (2023a) found that the cardiac function of STZ-induced diabetic rats was damaged, and AA could improve these damages.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%
“…Artemisinin and allicin (AA) have anticancer, antioxidant, and anti-inflammatory biological activities ( Zhou et al, 2022 ; Jin et al, 2023 ) and have been proved to be used in clinical anti-myocardial fibrosis ( Kong et al, 2023a ). Kong et al (2023a) found that the cardiac function of STZ-induced diabetic rats was damaged, and AA could improve these damages. In addition, the myocardial cells of diabetic rats showed pathological changes, such as increased collagen fibers, a large number of fibrous scars, and increased myocardial cells, and these changes were significantly reduced after AA intervention.…”
Section: Signaling Pathways In Tcm Intervening the Pathological Progr...mentioning
confidence: 99%